PERMOHONAN PAILIT PERUSAHAAN ASURANSI OLEH AGEN ASURANSI - Clarissa Tifanny Shafia Kusumastuti; Heru Pringgodani Sanusi (Fakultas Hukum Universitas Trisakti, 2022)
The relationship between insurance agent and insurance company is written in an agency agreement, in which there is an explanation regarding the distribution of fee payments as the rights of insurance agent and the obligations of the insurance company. But the relationship between the insurance agent and the insurance company does not always go well when the insurance agent submits a payment for their services, which leads to filing of a bankruptcy petition to the Commercial Court. In filing an application for bankruptcy of an insurance company, the method is different from filing an application for bankruptcy against ordinary individuals or companies. This research discusses how the procedure for applying bankruptcy statement from insurance company that should be according to Bankruptcy and Insurance Law. This is a normative and descriptive analytical legal research, using literature study method and in the results of the research there are several regulations regarding filing bankruptcy applications regulated in Law 37/2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, Law 21/2011 concerning the Financial Services Authority, Law 40/2007 concerning Limited Liability Companies, Law 40/2014 concerning Insurance, and POJK 28/POJK.05/2015 concerning Dissolution and Bankruptcy of Insurance Companies, Sharia Insurance Companies, Reinsurance Companies, and Sharia Reinsurance Companies.